1985
DOI: 10.1128/jvi.56.2.571-578.1985
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a new serotype of simian acquired immune deficiency syndrome type D retrovirus from Celebes black macaques (Macaca nigra) with immune deficiency and retroperitoneal fibromatosis

Abstract: A new serotype of simian acquired immune deficiency syndrome (SAIDS) retrovirus (type 2) belonging to the D genus of retroviruses is associated with a SAIDS occurring spontaneously in a colony of Celebes macaques (Macaca nigra) and rhesus macaques (Macaca mulatta) at the Oregon Regional Primate Research Center. This syndrome resembles SAIDS in M. mulatta at the California Primate Research Center, which is associated with a similar type D retrovirus (type 1). However, at the Oregon Center, SAIDS is distinguishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Serum specimens were tested for neutralizing activity, according to the procedures described by Marx et al (10), with modifications. The neutralization titer was determined in Vero E6 cells.…”
Section: Neutralization Testmentioning
confidence: 99%
“…Serum specimens were tested for neutralizing activity, according to the procedures described by Marx et al (10), with modifications. The neutralization titer was determined in Vero E6 cells.…”
Section: Neutralization Testmentioning
confidence: 99%
“…Three types of type-D retrovirus have been isolated from macaques. These were associated epidemiologically or experimentally with simian acquired immune deficiency syndrome (SAIDS) (Fine et al, 1975;Marx et al, 1984Marx et al, , 1985Bryant et al, 1986). Simian type-D retroviruses include Mason-Pfizer monkey virus (MPMV) and SAIDS retrovirus, types 1 and 2 (SRV-1 and SRV-2).…”
mentioning
confidence: 99%
“…In human cells, human ASCT2 is a functional receptor for pathogenic retroviruses, such as simian retrovirus (SRV) 1, 2, 3, 4 and 5, avian reticuloendotheriosis virus, and duck spleen necrosis virus [35]. It is known that SRV-1, SRV-2 and SRV-3 induce a fatal immunodeficiency in some macaque species (Celebes and rhesus macaques) [21][22][23]. In a previous study, we confirmed that both SRV-2 and SRV-3 can utilize canine ASCT2 as a receptor ( [51], unpublished data).…”
Section: Contamination Of Live Attenuated Vaccines 401mentioning
confidence: 99%